Systemic Inflammation and Reperfusion Injury in Patients With Acute Myocardial Infarction - Blancke, Fien (Hindawi Publishing Corporation, 2005)
Despite early recanalization of an occluded infarct artery, tissue reperfusion remains impaired in more than one-third of the acute myocardial infarction (AMI) patients owing to a process of reperfusion injury. The role of systemic inflammation in triggering this phenomenon is unknown. Proinflammatory factors (hs-CRP, TNF-α) and anti-inflammatory mediators (IL-1 receptor antagonist, IL-10) were measured in 65 patients during the acute phase of a myocardial infarction as well as in 11 healthy control subjects. Myocardial reperfusion injury was defined as the presence of persistent ST-segment elevation despite successful coronary intervention (≥ 50% of the initial value) and was observed in 28 patients. Systemic proinflammatory mediators (particularly hs-CRP and leukocytes) were higher in AMI patients compared to control subjects. Within the group of AMI patients, only serum TNF-α differed significantly between patients with versus without reperfusion injury: a median value of 25 versus 13 pg/mL was observed, respectively. Logistic regression analysis identified a high level of TNF-α as the most important independent determinant of reperfusion injury (P = .001), beyond total ischemic time (P = .01) and extent of jeopardized myocardium (P = .08). There was no correlation between the TNF-α level and the total ischemic time (P = .8) or the extent of jeopardized myocardium (P = .6). Systemic inflammation, in particular high levels of TNF-α, is strongly associated with the occurrence of reperfusion injury after successful recanalization. Our findings suggest that TNF-α is involved in the triggering and/or amplification of local inflammatory responses related to ischemia-reperfusion injury.